1973
DOI: 10.1055/s-0028-1096734
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Serotonin Induced GH Secretion in Rats by Melatonin and Cyproheptadine

Abstract: 5-Hydroxy-L-tryptophan is a potent stimulus for growth hormone (GH) secretion in normal rats. This stimulus is completely blocked by melatonin and also by the serotonin antagonist, cyproheptadine.Materiala ancl Methods Groups of non-handled male and female Wistar rats 80 days old were injected intraperitoneally with the following drugs or drug combinations dissolved in 0.5 ml physiological saline containing 20% v/v ethanol: 5-hydroxy-L-tryptophan (5-HTP, 10 mg/kg); 5-HTP (10 mg/kg) plus melatonin (80 mg/kg); 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1974
1974
1996
1996

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Melatonin was selected as a possible inhibitor of brain serotonin receptors in this investigation and in studies on rat GH secretion (7)(8)(9) because it is an 0-methylated derivative of serotonin. We have previously hypothesized (21) and recently shown (22,23) that 0-methylation of dopamine results in derivatives that inhibit the actions of dopamine by competing for its hypothalamic receptor sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin was selected as a possible inhibitor of brain serotonin receptors in this investigation and in studies on rat GH secretion (7)(8)(9) because it is an 0-methylated derivative of serotonin. We have previously hypothesized (21) and recently shown (22,23) that 0-methylation of dopamine results in derivatives that inhibit the actions of dopamine by competing for its hypothalamic receptor sites.…”
Section: Discussionmentioning
confidence: 99%
“…Collu, Fraschini, Visconti, and Martini (6) have demonstrated that intraventricular administration of serotonin causes GH release in the rat. Our studies (7)(8)(9) have shown that rat GH secretion is stimulated by intraperitoneal administration of 5-HTP and, furthermore, that it is inhibited by serotoninergic blockade and also by the pineal gland hormone, melatonin, which appears to act by competing with ser-otonin for serotonin receptor sites (9). The GH release observed in humans after the onset of slow-wave sleep (10) has also been suggested to originate via serotoninergic pathways (3,11).…”
Section: Introductionmentioning
confidence: 99%
“…High doses of melatonin (SO mg/kg) reportedly suppress the secretion of growth hormone (GH) (115,116); this action may be related to the effect of melatonin on brain serotonin levels (117). It has also been reported that melatonin decreases the somatomedin-like activity of rat plasma (11S).…”
Section: Other Glandsmentioning
confidence: 96%